Hoya tamdaoensis (Apocynaceae, Asclepiadoideae), a new species from Vietnam - Rodda, Michele; Tran, The Bach; Nguyen, Quoc Binh (Phytotaxa, 2015)
A new species of Hoya R.Br. from Tam Đảo National Park (Vĩnh Phúc Province, Vietnam), Hoya tamdaoensis Rodda & T.B.Tran,is described and illustrated. It is distinguished from the morphologically similar Hoya siamica Craib by corolla size, lamina shape, coloration, and orientation of the petioles.